The Help of God and Fear of Man: Comparing Anxiety and Religiosity in Fury (2014) and Merah-Putih (2009) - Sampurno, Muhammad Faqih (Journal of Language and Literature, 2023)
This research aims at investigating the influence of religiosity on anxiety during the war. This research compares two contrasting military leader characters to identify the influence on the way that these characters cope with war-induced anxiety.  The main comparative objects are the characters Don from the movie Fury (2014) and Amir in Merah-Putih (2009). Both characters show similar anxiety and religiosity but differ in how they cope with anxiety. The general assumption is that religiosity helps to cope with anxiety. This research uses Freud’s psychoanalysis theory to study the characters. By comparing these characters, we may find the relation of religiosity towards anxiety, and we may also find other influences such as the character’s motivation and backstory. The five dimensions of religiosity, as explained by Glock Stark and Freud’s psychoanalytic theory on anxiety, determine religiosity and anxiety. The variables are expressed through practice, discourse, and symbols by both characters in scenes and dialogues. The findings are listed in three items: 1) The coping mechanism for anxiety works not only to repress but also to create new anxiety. 2) The new anxiety can be so much worse than the initial anxiety. 3) Religiosity is not a necessary variable in dealing with anxiety. Additionally, the founding of new anxiety contributes to previous theory on anxiety.